The gearing adjustment in inflation accounting: The financing sequence assumption - M. A. Van Hoepen; I. J. Lambrechts; F. J. Mostert (South African Journal of Business Management, 1989)
The application of a gearing adjustment in inflation accounting has always resulted in the problem of determining a financing sequence. A decision has to be taken whether certain categories of assets are financed with equity and/or loan capital. Financial theory of the last few decades quite convincingly revealed that there are no logical grounds for relating certain assets to certain liabilities and/or equity. This proportional financing assumption is discussed and illustrated in the article for the so-called Van der Schroeff-system of income demermination in order to point out the sensitivity and financial consequences of this assumption for financial decision making. The assumption about the financing sequence does have a definite influence on the gearing adjustment. Further influences are on the income statement and the message given to shareholders and the investment public; the composition of the asset structure and consequently the risk composition of the assets; the composition of the financing structure and consequently the financial risk as portrayed by the balance sheet; and the marginal financing ratios needed to maintain the original gearing ratio.